Compositional and Thermal Effects on the Phase Stability and Crystallinity of Cu₂SnS₃ Nanoparticles - Ismail, Agus; Nurika, Destia; Wismogroho, Agus Sukarto; Amal, Muhammad Ikhlasul (Akta Kimia Indonesia, 2025)
Cu₂SnS₃ (CTS) is a promising semiconductor for photovoltaic applications, yet its synthesis via solid-state sintering remains insufficiently explored. This study examines the phase evolution and structural properties of CTS thin films fabricated from Cu, Sn, and S elemental precursors sintered at 300 °C, 400 °C, 500 °C, and 600 °C. X-ray diffraction (XRD) analysis confirmed that stoichiometric CTS attained optimal phase purity at 500°C, whereas off-stoichiometric compositions resulted in secondary phases such as Cu₂S, Cu₉.₆₇Sn₂.₃₃S₁₃, and SnS₂. Scanning electron microscopy (SEM) revealed microstructural transformations, with well-defined crystalline domains emerging at 500°C but excessive grain coalescence in Cu-rich samples. Energy-dispersive X-ray spectroscopy (EDX) verified compositional variations, underscoring the critical role of stoichiometry in phase stability. These findings demonstrate that precise compositional control and optimized sintering conditions are essential for high-purity CTS films, advancing their potential for enhanced photovoltaic performance and long-term operational stability.